Dark skin glaze ceramic tile and preparation method thereof

Through a three-layer glaze structure design, the high-alumina and high-zirconium surface glaze layer blocks impurities, the barium-zinc-calcium-magnesium skin glaze layer optimizes color development, and the protective glaze layer enhances acid and alkali resistance and hardness. This solves the technical bottleneck of traditional skin glaze tiles in dark applications, achieving stable dark color development and high-performance glaze effects.

CN120923266APending Publication Date: 2025-11-11ZHUHAI WHITE RABBIT CERAMICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511060443.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Traditional skin-glazed ceramic tiles suffer from problems such as impurity migration leading to a lighter color, insufficient saturation, and easy wear of the glaze when used in dark applications. They also have a shorter lifespan in acid and alkali corrosion and friction scenarios.

Method used

It adopts a three-layer glaze structure, including a high-alumina and high-zirconium top glaze layer to block impurities, a barium-zinc-calcium-magnesium skin glaze layer to optimize the color development environment, and a protective glaze layer to provide an apatite-calcium feldspar-zircon crystal phase network, thereby improving the acid and alkali resistance and hardness of the glaze surface.

Benefits of technology

It achieves stability in dark color and preservation of satin texture, the glaze has an acid and alkali resistance rating of AA, no cracking after 10 thermal shock cycles, and a hardness of ≥6, meeting the comprehensive needs of high-end architectural decoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120923266A_ABST
    Figure CN120923266A_ABST
Patent Text Reader

Abstract

The invention discloses a dark skin glaze ceramic tile and a preparation method thereof, and relates to the technical field of ceramic tiles. The dark skin glaze ceramic tile comprises a bottom blank, a cover glaze layer, a skin glaze layer, an ink printing layer and a protective glaze layer, and the chemical composition of the cover glaze layer comprises Al2O3, SiO2, ZrO2, K2O, Na2O, CaO and MgO; the chemical composition of the skin glaze layer is prepared from SiO2, Al2O3, BaO, ZnO, CaO, MgO, K2O and Na2O; the protective glaze layer is prepared from the following raw materials: potassium feldspar, quartz, calcite, bone ash, kaolin and zirconium silicate. According to the invention, a three-layer functional layered glaze structure is successfully constructed, the problem of dark color and chromatic aberration of traditional skin glaze is solved, the color development of the ink reaches the level of bright glaze, and 10-15-degree satin texture is reserved; and the glaze surface has acid and alkali resistance reaching AA level, is free of cracking in thermal shock cycle, and has excellent flatness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic technology, and in particular to a dark skin-colored glazed ceramic tile and its preparation method. Background Technology

[0002] In the field of building decoration materials, ceramic tiles, as the core material for wall and floor decoration, have always been a key focus of industry research and development in terms of performance and decorative effect. With consumption upgrades and diversified aesthetics, the market demand for ceramic tiles has shifted from basic functions to "high quality, personalization, and scene adaptation." Among them, dark-colored textured ceramic tiles, which can create an elegant and dignified spatial atmosphere, are in high-end hotels, office buildings, and boutique residences, where demand continues to grow.

[0003] Traditional skin-like glaze ceramic tiles hold an important position in the field of light-colored decoration due to their soft satin-like texture (gloss level 10-15°) and delicate touch. However, they face significant technical bottlenecks in dark-colored applications. On the one hand, the traditional single-layer glaze structure cannot prevent the migration of impurities such as iron and titanium in the body, which leads to interference from impurities when the ink is applied, resulting in problems such as light color, insufficient saturation, and grayscale distortion. On the other hand, the physical and chemical properties of single-layer glaze are limited. In environments such as kitchens and bathrooms where they are susceptible to acid and alkali corrosion and friction, problems such as glaze wear and contamination can easily occur, resulting in a shorter service life.

[0004] Therefore, developing a technical solution that can preserve the glossy texture of skin glaze, solve the problem of dark coloring, and improve the performance of glaze has become the key for the ceramic industry to break through technical bottlenecks and meet market demands.

[0005] It is evident that existing technologies still need improvement and enhancement. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a dark skin-colored glaze ceramic tile and its preparation method, which aims to solve the problem that existing skin-colored glaze ceramic tiles are difficult to maintain a stable dark color and better physicochemical properties while retaining the satin texture of skin glaze.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] A dark skin-colored glaze ceramic tile includes a base, a surface glaze layer, a skin-colored glaze layer, an ink printing layer, and a protective glaze layer. The surface glaze layer's chemical composition, by mass percentage, includes: 25-30% Al₂O₃, 50-60% SiO₂, 1-5% ZrO₂, 1-3% K₂O, 3-6% Na₂O, 1-3% CaO, 0.5-1% MgO, 0.1-0.3% Fe₂O₃, 0.05-0.15% TiO₂, and 1-3% loss on ignition. The skin-colored glaze layer's chemical composition... The composition, by mass percentage, includes: 40-50% SiO2, 14-16% Al2O3, 6-10% BaO, 3-5% ZnO, 4-6% CaO, 4-6% MgO, 3-5% K2O, 1-3% Na2O, and 6-10% loss on ignition; the raw materials of the protective glaze layer, by mass percentage, include: 35-45% potassium feldspar, 15-25% quartz, 10-20% calcite, 5-15% bone ash, 3-8% kaolin, and 5-15% zirconium silicate.

[0009] The aforementioned dark skin-colored glaze ceramic tile, wherein the chemical composition of the surface glaze layer, by mass percentage, comprises: 28.38% Al₂O₃, 56.90% SiO₂, 2.61% ZrO₂, 1.77% K₂O, 4.32% Na₂O, 2.06% CaO, 0.92% MgO, 0.15% Fe₂O₃, 0.1% TiO₂, and 2.79% loss on ignition; the chemical composition of the skin-colored glaze layer, by mass percentage, comprises... The protective glaze contains 46.49% SiO2, 15.64% Al2O3, 8.48% BaO, 3.98% ZnO, 5.44% CaO, 5.31% MgO, 4.03% K2O, 1.56% Na2O, and 9.07% loss on ignition; the raw materials of the protective glaze, by mass percentage, include 40% potassium feldspar, 20% quartz, 15% calcite, 10% bone ash, 5% kaolin, and 10% zirconium silicate.

[0010] A method for preparing a dark skin-colored glazed ceramic tile as described in this invention, comprising the steps of:

[0011] The chemical composition of the glaze layer is fed into a ball mill according to the formula ratio, and deionized water is added for ball milling to obtain the glaze slurry.

[0012] The chemical composition of the skin glaze is put into a ball mill according to the formula ratio, and deionized water is added for ball milling to obtain skin glaze slurry.

[0013] The raw materials for the protective glaze are put into a ball mill according to the formula ratio, and deionized water is added for ball milling to obtain the protective glaze slurry.

[0014] A glaze slurry is applied to the surface of the body using a glazing process, and a glaze layer is formed after drying.

[0015] A skin-like glaze is applied to the surface of the glaze layer using a glazing process, and after drying, a skin-like glaze layer is formed.

[0016] Ink is printed onto the surface of the skin's enamel layer using inkjet printing to form an ink-printed layer.

[0017] A water jet sprayer is used to apply the protective glaze slurry to the surface of the printed blank, which then dries to form a protective glaze layer.

[0018] The body with the protective glaze layer is fired to obtain the dark skin glaze ceramic tile.

[0019] The method for preparing the dark skin-colored glazed ceramic tile includes the following step: in the preparation of the surface glaze slurry, the chemical composition of the surface glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.4, and ground until the residue passing through a 300-mesh sieve is less than or equal to 0.5%. The specific gravity of the surface glaze slurry is adjusted to 1.85-1.9 g / cm³. 3 spare.

[0020] The method for preparing the dark skin-colored glaze ceramic tile includes, in the step of preparing the skin-colored glaze slurry, the chemical composition of the skin-colored glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.35, and ground until the residue passing through a 200-mesh sieve is less than or equal to 0.8%, and the specific gravity of the skin-colored glaze slurry is adjusted to 1.85-1.9 g / cm³. 3 spare.

[0021] In the method for preparing the dark skin glaze ceramic tile, in the step of printing ink on the surface of the skin glaze layer by inkjet printing to form an ink printing layer, the printing parameters are set according to the characteristics of the ink, with the nozzle temperature at 40-45℃ and the jet pressure at 0.3-0.5MPa.

[0022] The method for preparing the dark skin-colored glazed ceramic tile includes the following step: In the preparation of the protective glaze slurry, the chemical composition of the protective glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.3, and ground until the residue passing through a 250-mesh sieve is less than or equal to 1%. The specific gravity of the protective glaze slurry is adjusted to 1.2-1.4 g / cm³. 3 spare.

[0023] The method for preparing the dark skin glaze ceramic tile includes a firing process for the body forming the protective glaze layer, comprising a heating stage, a holding stage, and a cooling stage. In the heating stage, the temperature is increased to 1220-1250℃ at a heating rate of 5℃ / min. In the holding stage, the temperature is held at 1220-1250℃ for 10-20min. In the cooling stage, the body is cooled to room temperature in the furnace.

[0024] Beneficial effects: This invention uses a high-alumina, high-zirconium glaze layer to block impurities in the body, and a barium-zinc-calcium-magnesium skin glaze to optimize the color development environment, achieving ink color saturation comparable to traditional glossy glazes, breaking through the technical limitations of traditional skin glazes' light color limitation; the submicron liquid-phase separation structure of the skin glaze layer retains a 10-15° satin texture and delicate touch, while the introduction of ZnO stabilizes the ink color development environment, resolving the core contradiction between texture preservation and dark color development; the apatite-calcium feldspar-zircon crystal phase network provided by the protective glaze layer of this invention can achieve an acid and alkali resistance level of AA, no cracking after 10 thermal shock cycles, and a hardness of ≥6 without affecting transparency, meeting the needs of complex scenarios; this invention also achieves precise matching of the thermal expansion coefficient and melting temperature of the three glaze layers through formula and process design, with tight interlayer bonding, eliminating the risk of cracking and peeling. The dark skin-colored glaze ceramic tile provided by this invention fills the gap in the field of dark textured ceramic tiles in traditional technology, and meets the comprehensive needs of high-end architectural decoration for texture, dark color and performance; the product is both decorative and durable, and can be widely used in high-end hotels, office buildings, boutique residences and other scenarios, especially in areas with high performance requirements such as kitchens and bathrooms. Attached Figure Description

[0025] Figure 1 This is a flowchart illustrating the preparation method of a dark skin-colored glazed ceramic tile according to the present invention.

[0026] Figure 2 This is a photograph of the dark skin-colored glazed ceramic tile prepared in Example 1 of the present invention.

[0027] Figure 3 This is a photograph of the dark skin-colored glazed ceramic tile prepared in Example 2 of the present invention.

[0028] Figure 4 This is a photograph of the dark skin-colored glazed ceramic tile prepared in Example 3 of the present invention.

[0029] Figure 5 This is a physical image of the ceramic tile prepared in Comparative Example 1 of the present invention.

[0030] Figure 6 This is a physical image of the ceramic tile prepared in Comparative Example 2 of the present invention.

[0031] Figure 7 This is a physical image of the ceramic tile prepared in Comparative Example 3 of the present invention. Detailed Implementation

[0032] This invention provides a dark-colored skin-toned glazed ceramic tile and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following embodiments are provided to further illustrate the invention in detail. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0033] This invention provides a dark skin-colored glaze ceramic tile, comprising a base, a surface glaze layer, a skin-colored glaze layer, an ink printing layer, and a protective glaze layer. The surface glaze layer, by mass percentage, comprises: 25-30% Al₂O₃, 50-60% SiO₂, 1-5% ZrO₂, 1-3% K₂O, 3-6% Na₂O, 1-3% CaO, 0.5-1% MgO, 0.1-0.3% Fe₂O₃, 0.05-0.15% TiO₂, and 1-3% loss on ignition; the skin-colored glaze layer... The chemical composition, by mass percentage, includes: 40-50% SiO2, 14-16% Al2O3, 6-10% BaO, 3-5% ZnO, 4-6% CaO, 4-6% MgO, 3-5% K2O, 1-3% Na2O, and 6-10% loss on ignition; the raw materials of the protective glaze layer, by mass percentage, include: 35-45% potassium feldspar, 15-25% quartz, 10-20% calcite, 5-15% bone ash, 3-8% kaolin, and 5-15% zirconium silicate.

[0034] This invention achieves the technical effects of stable dark color development, preservation of satin finish, and improved physicochemical properties through the formulation design and dosage control of a three-layer "functional layered" glaze structure. Its core mechanism, from the perspective of formulation components and dosage, can be divided into two parts: the individual and synergistic effects of the surface glaze layer, the skin glaze layer, and the protective glaze layer, as detailed below:

[0035] The core function of the glaze layer in this invention is to prevent coloring impurities such as Fe2O3 and TiO2 in the green body from migrating to the surface, providing a clean and undisturbed canvas for ink printing. Its formulation and dosage are crucial to achieving this function. In the glaze layer, Al2O3 is the core skeletal component; a dosage of 25-30% can significantly improve the glaze layer density. During firing, Al2O3 forms an aluminosilicate glass phase with SiO2, with a tightly packed molecular structure that can physically block Fe2O3 from migrating from the green body. 3+ Ti 4+ The presence of diffusion channels for impurity ions ensures that the migration of impurities in the body can be controlled below 0.01%. ZrO2, a typical chemically inert component with a Mohs hardness of 8, not only enhances the mechanical strength of the glaze but also stabilizes the glass phase structure through a "lattice locking" effect, reducing the penetration rate of impurity ions. Experimental data show that at a dosage of 1-5%, the impact of body impurities on surface color is reduced by more than 90%, solving the problem of dark graying caused by impurity contamination in traditional single-layer glazes.

[0036] In the glaze layer, SiO2 serves as the main glassy phase. A dosage of 50-60% can construct a stable network structure. Excessive dosage will lead to excessively high melting temperatures in the glaze, easily causing underfiring. Insufficient dosage will cause crystallization in the glaze layer, affecting its smoothness. At this dosage, SiO2 forms a rigid network with Al2O3 and ZrO2, ensuring both the density required to block impurities and sufficient melting at the firing temperature, thus preventing pinholes and bubbles from appearing on the glaze surface.

[0037] In the glaze layer, alkali metal oxides K₂O and Na₂O act as fluxes, reducing the melt viscosity of the glaze and ensuring that the glaze evenly covers the body during the glazing process. Alkaline earth metal oxides CaO and MgO help regulate the coefficient of thermal expansion, making the coefficients of thermal expansion of the glaze and the body similar, thus preventing cracking after firing. The synergistic use of these two materials solves the problems of difficult melting and glaze shrinkage in high-alumina, high-zirconium formulations, while also ensuring the density of the glaze layer.

[0038] This invention's skin-like glaze layer is the core layer balancing satin finish and stable dark color development. Its formulation, through controlled use of barium, zinc, calcium, and magnesium components, forms a submicron liquid-phase separation structure (preserving the satin finish) while providing a stable color development environment for inks. In the skin-like glaze layer, BaO acts as a liquid-phase separation inducer; a dosage of 6-10% promotes submicron-level separation of silicon-rich and barium-rich phases during firing. This structure diffuses light, stabilizing the gloss at 10-15°, consistent with the satin finish characteristics of skin-like glazes. CaO and MgO assist in regulating the uniformity of liquid-phase separation. CaO promotes the continuity of phase separation, avoiding roughness caused by excessive local separation; MgO reduces the coarsening rate of phase separation, ensuring a fine microstructure (silky smooth feel). BaO (6-10%), CaO (4-6%), and MgO (4-6%) constitute the submicron liquid-phase separation structure, preserving the satin finish. Experiments show that at this dosage, the standard deviation of skin glaze gloss is ≤1° and the tactile roughness is ≤0.05μm.

[0039] In the skin's glaze layer, ZnO acts as a color stabilizer; a dosage of 3-5% can optimize dark colors through two pathways: chemical anchoring: Zn 2+ It forms stable coordination structures (such as Zn-Fe-O complex bonds) with pigment ions in inks (e.g., iron black, cobalt blue), reducing pigment volatilization or dissolution at high temperatures (pigment loss rate reaches 20% in traditional single-layer glazes, but can be reduced to below 5% with this dosage); it also adjusts the pH of the glaze: ZnO makes the glaze weakly alkaline after firing, at pH 7.5-8.0, avoiding pigment fading caused by acidic environments. For example, iron black pigment is easily oxidized to light brown in acidic glazes, but it remains pure black in this system. A dosage of 3-5% ensures color stability without interfering with the liquid-phase separation structure.

[0040] In the skin-like glaze layer, SiO2 provides a glassy matrix for liquid-phase separation, while Al2O3 enhances the mechanical strength of the glaze layer, preventing scratches on the glaze surface during inkjet printing. Their synergistic use ensures that the glaze has sufficient fluidity after firing, resulting in uniform liquid-phase separation, while also providing a certain degree of rigidity to support pigment adhesion. If the Al2O3 content is too high (e.g., exceeding 20%), it will lead to insufficient liquid-phase separation (gloss dropping below 8°); if it is too low (e.g., below 12%), the glaze layer is prone to over-melting, and the satin finish will turn into a semi-matte finish. SiO2 and Al2O3 work together to construct the structural framework, balancing texture and strength.

[0041] In the skin glaze layer, the amount of K2O and Na2O used works synergistically with the glaze to ensure that the skin glaze layer can be evenly covered on the surface of the glaze layer without dripping or uneven thickness.

[0042] The core function of the protective glaze layer in this invention is to improve the chemical stability, thermal stability and hardness of the glaze without affecting the texture and color of the underlying layer. Its formula introduces the apatite crystal phase through bone ash, and, in conjunction with the controlled amount of zirconium silicate and calcite, constructs a transparent reinforcing network.

[0043] In the protective glaze layer, the main component of bone ash is calcium phosphate (Ca3(PO4)2), and its 5-15% content can react with the Ca from calcite in the glaze during the firing process. 2+ Si from quartz 4+ The reaction forms an apatite crystalline phase (Ca5(PO4)3(OH)). This apatite crystalline phase is extremely chemically inert; its resistance to corrosion from 1% HCl and 1% NaOH is three times that of the traditional glassy phase, achieving AA-grade acid and alkali resistance. Its crystal form is hexagonal prismatic, and when uniformly dispersed within the glassy phase, it exhibits extremely low light scattering (transmittance ≥85%), preventing obstruction of the underlying color development. If the amount of bone ash used is too high (e.g., exceeding 15%), excessive growth of the apatite crystalline phase (particle size >5μm) will lead to decreased transmittance, affecting color development. Conversely, if the amount of bone ash used is too low (e.g., below 5%), insufficient crystalline phase will result in inadequate chemical stability.

[0044] In the protective glaze layer, zirconium silicate (ZrSiO4) has a Mohs hardness of 7. A dosage of 5-15% can act as a hard reinforcing phase, uniformly dispersed within the glaze layer, increasing the surface hardness from the traditional skin-like glaze of level 5 to level 6 or higher (resisting scratches from everyday hard objects). Simultaneously, zirconium silicate synergizes with apatite crystals: Zr... 4+ It can inhibit the excessive growth of the apatite crystal phase and avoid a decrease in light transmittance, while apatite helps to uniformly disperse zirconium silicate and avoid "white spot" defects caused by agglomeration. Experiments show that at this dosage, the glaze surface is free of scratches and does not affect the color development of the underlying layer.

[0045] In the protective glaze layer, calcite decomposes into CaO during firing (providing Ca). 2+A dosage of 10-20% can react with Al2O3 and SiO2 in potassium feldspar to form anorthite crystal phase (CaAl2Si2O8): the thermal expansion coefficient of anorthite is 6.5 × 10⁻⁶. -6 (℃) It matches the body, surface glaze, and skin glaze, and can absorb the stress during thermal shock; its needle-like crystal form can form an interwoven structure with apatite and zirconium silicate, enhancing the glaze layer's resistance to thermal shock. If the dosage is less than 10%, insufficient anorthite formation will occur, and thermal stability will decrease; if the dosage is more than 20%, it will easily lead to excessive crystallization on the glaze surface and a decrease in light transmittance.

[0046] In the protective glaze layer, potassium feldspar (35-45%) forms the main glassy phase, providing fluidity to ensure a smooth glaze layer; quartz (15-25%) adjusts the refractive index of the glassy phase, preventing light reflection at the interface and affecting transparency. The synergistic use of these two components allows the protective glaze to form a crystalline strengthening network while maintaining a light transmittance of over 85%, ensuring that the underlying color development and satin finish are not obscured, thus solving the problem of traditional protective glazes inevitably blocking light as they harden.

[0047] In this invention, the technical effect of the three-layer glaze structure—the surface glaze, the inner glaze, and the protective glaze—is not achieved by a single glaze layer, but through cross-layer synergy of formulation components and dosages. The core matching logic is as follows: matching of thermal expansion coefficients. In the surface glaze, Al2O3 and ZrO2 reduce the thermal expansion coefficient; in the inner glaze, BaO and ZnO are adjusted to intermediate values; and in the protective glaze, calcite and zirconium silicate are increased to match the body. Ultimately, the difference in thermal expansion coefficients between the three glaze layers and the body is ≤1×10⁻⁶. -6 / ℃, to avoid interlayer cracking after firing. Matching melting temperatures: the top glaze layer, due to its high alumina and zirconium content, requires a higher melting temperature (1230℃), the skin glaze layer is lowered to 1220-1230℃ using BaO, and the protective glaze is adjusted to 1210-1230℃ using potassium feldspar. All three melt and combine synchronously during the firing cycle, preventing any layer from over-melting or under-firing. Synergistic transparency: the high alumina and zirconium formula in the top glaze layer ensures no impurities interfere (pure base color), the liquid-phase separation structure (BaO) in the skin glaze layer controls diffuse light reflection and preserves texture, and the low-opacity crystalline phase (bone ash + zirconium silicate) in the protective glaze layer ensures light penetration, ultimately ensuring that the underlying color is not obscured and the satin finish is not weakened.

[0048] In summary, this invention achieves ink color saturation comparable to traditional glossy glazes by using a high-alumina, high-zirconium glaze layer to block impurities in the body and a barium-zinc-calcium-magnesium skin glaze to optimize the color development environment, thus overcoming the technical limitations of traditional skin glazes that restrict light colors. The submicron liquid-phase separation structure of the skin glaze layer retains a 10-15° satin finish and delicate touch, while the introduction of ZnO stabilizes the ink's color development environment, resolving the core contradiction between texture preservation and dark color development. The apatite-calcium feldspar-zircon crystal phase network provided by the protective glaze layer allows the glaze to achieve an AA-level acid and alkali resistance rating, remain crack-free after 10 thermal shock cycles, and have a hardness ≥6 without affecting transparency, meeting the needs of complex scenarios. Furthermore, through formula and process design, the thermal expansion coefficients and melting temperatures of the three glaze layers are precisely matched, achieving tight interlayer bonding and eliminating the risk of cracking and peeling. The dark skin-colored glaze ceramic tile provided by this invention fills the gap in the field of dark textured ceramic tiles in traditional technology, and meets the comprehensive needs of high-end architectural decoration for texture, dark color and performance; the product is both decorative and durable, and can be widely used in high-end hotels, office buildings, boutique residences and other scenarios, especially in areas with high performance requirements such as kitchens and bathrooms.

[0049] In some embodiments, the ink chemical composition of the ink printing layer includes, by mass percentage: 20-40% pigment, 40-60% organic solvent, 3-10% dispersant, 5-10% humectant, and 1-3% pH adjuster, but is not limited thereto. In this embodiment, the pigment is one or more of iron-based pigment, cobalt-based pigment, and chromium-based pigment, but is not limited thereto; the organic solvent is one of ethylene glycol and isopropyl palmitate; the humectant is glycerol; and the pH adjuster is ammonia, but is not limited thereto. As an example, the iron-based pigment includes iron black pigment, which uses iron(III) oxide (Fe3O4) or zinc ferrite (ZnFe2O4) as the main component, and controls the valence state of iron ions (Fe... 2+ with Fe 3+ (Collaborative) to achieve a black tone; cobalt-based pigments include cobalt blue pigment, which is mainly composed of cobalt aluminum spinel (CoAl2O4), through cobalt ions (Co... 2+ The stable presence of chromium achieves a blue hue; chromium-based pigments include chrome green / chrome black pigments, which are mainly composed of cobalt chromate (CoCr2O4) or chrome iron black (FeCr2O4), and are produced through the ionization of chromium (Cr) ions. 3+ It works in conjunction with other metal ions to achieve green or gray-black tones.

[0050] The "darkness" in this invention's dark-skin glaze ceramic refers to the relatively high grayscale when ink is applied to the glaze surface using an inkjet printer after adjusting the file in Photoshop. The conventional understanding is that higher grayscale means a deeper color. However, in the case of glaze with a matte finish, the metallic color-producing ions in the ink are eroded at high temperatures, resulting in a lighter color. The reason for the relatively light color in conventional glazes with a matte finish is that they typically use two layers of glaze. The first layer provides a base for the inkjet pattern, similar to a canvas in painting. The second layer provides the skin-like feel and physicochemical properties. However, the second layer must be relatively thick to achieve the skin-like feel. But glazes with a certain degree of opacity can cover the ink, and the glaze itself can erode the ink, preventing the color from developing. If a top glaze is sprayed first, followed by a skin-like glaze, the color will be darker, but the ink pattern exposed on the surface will be worn away. The approach of this invention is to first spray the top glaze layer and the skin-like glaze layer, then apply the pattern. This results in a deeper color. Finally, a very thin layer of transparent protective glaze is sprayed to achieve the physical and chemical properties of the ceramic tile. It should be noted that the inks used in this invention are all commercially available inks, and the colors can be adjusted according to requirements.

[0051] In some embodiments, a specific dark-colored skin-glazed ceramic is also provided, comprising a base, a surface glaze layer, a skin-colored glaze layer, an ink printing layer, and a protective glaze layer, wherein the chemical composition of the surface glaze layer, by mass percentage, comprises: 28.38% Al₂O₃, 56.90% SiO₂, 2.61% ZrO₂, 1.77% K₂O, 4.32% Na₂O, 2.31% CaO, 0.92% MgO, and 2.79% loss on ignition; the chemical composition of the skin-colored glaze layer... The composition, by weight percentage, includes: 46.49% SiO2, 15.64% Al2O3, 8.48% BaO, 3.98% ZnO, 5.44% CaO, 5.31% MgO, 4.03% K2O, 1.56% Na2O, and 9.07% loss on ignition; the raw materials of the protective glaze layer, by weight percentage, include: 40% potassium feldspar, 20% quartz, 15% calcite, 10% bone ash, 5% kaolin, and 10% zirconium silicate.

[0052] In some embodiments, a method for preparing dark-colored skin-glazed ceramics is also provided, such as... Figure 1 As shown, it includes the following steps:

[0053] S10. The chemical composition of the glaze layer is put into a ball mill according to the formula ratio, and deionized water is added for ball milling to obtain the glaze slurry.

[0054] S20. The chemical composition of the skin glaze is put into a ball mill according to the formula ratio, and deionized water is added for ball milling to obtain skin glaze slurry.

[0055] S30. Add the raw materials for the protective glaze layer into a ball mill according to the formula ratio, add deionized water and ball mill to obtain the protective glaze slurry.

[0056] S40. Apply a surface glaze slurry to the surface of the body using a glazing process, and form a surface glaze layer after drying.

[0057] S50. A skin-like glaze paste is applied to the surface of the glaze layer using a glazing process, and a skin-like glaze layer is formed after drying.

[0058] S60. Ink is printed onto the skin's enamel layer using inkjet printing to form an ink-printed layer.

[0059] S70. A water jet sprayer is used to apply the protective glaze slurry to the surface of the printed blank, and after drying, a protective glaze layer is formed.

[0060] S80. The body with the protective glaze layer is fired to obtain the dark skin glaze ceramic tile.

[0061] Specifically, in the preparation of the surface glaze slurry, the chemical composition of the surface glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.4, and ground until the residue passing through a 300-mesh sieve is less than or equal to 0.5%. The specific gravity of the surface glaze slurry is adjusted to 1.85-1.9 g / cm³. 3 spare.

[0062] In the preparation of the skin enamel slurry, the chemical composition of the skin enamel layer and deionized water are added to a ball mill at a mass ratio of 1:0.35, and ground until the residue passing through a 200-mesh sieve is less than or equal to 0.8%. The specific gravity of the skin enamel slurry is adjusted to 1.85-1.9 g / cm³. 3 spare.

[0063] In the step of preparing the protective glaze slurry, the chemical composition of the protective glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.3, and ground until the residue passing through a 250-mesh sieve is less than or equal to 1%. The specific gravity of the protective glaze slurry is adjusted to 1.2-1.4 g / cm³. 3 spare.

[0064] In the process of applying a glaze slurry to the surface of the green body using a glazing technique, and forming a glaze layer after drying, the following steps are taken: First, raw materials such as clay, quartz, and feldspar are weighed, crushed, and mixed evenly. The particle size distribution of the raw materials is controlled (D50 = 20-30μm) to ensure the plasticity of the green body. The mixed raw materials are then fed into a hydraulic molding machine, and a pressure of 120-150MPa is applied in a 600mm×1200mm mold to press them into a dense green body. After molding, defects such as cracks and missing corners are removed. The molded green body is then sent to a drying kiln and heated at a rate of 5℃ / min. Heat the kiln to 100-120℃ and dry for 50 minutes to reduce the moisture content of the green body to below 0.5%. During the drying process, the humidity inside the kiln needs to be monitored to avoid brick cracking during subsequent glazing due to residual moisture. Use a glazing process to apply a surface glaze slurry to the surface of the dried green body. For example, the amount of glaze applied is controlled to 100-120g (corresponding to a 400mm×600mm tray) to ensure uniform glaze coverage with a thickness of about 0.3mm. Dry at 180℃ for 15 minutes until the moisture content is ≤1% to form a surface glaze layer.

[0065] Next, a skin-like glaze is applied to the surface of the glaze layer using a glazing process. Similarly, the amount of glaze applied is controlled to be 100-120g (corresponding to a 400mm×600mm tray). The glaze forms a base layer with a submicron liquid phase separation structure through the high-temperature fluidity of the glaze. After drying, the skin-like glaze layer is formed.

[0066] Then, a high-precision inkjet printer is used to print an ink pattern on the surface of the skin glaze. The printing parameters are set according to the characteristics of the ink, with the printhead temperature at 40-45℃ and the jet pressure at 0.3-0.5MPa, to avoid ink bleeding or uneven coloring due to high ink grayness. After inkjet printing, the ink is quickly dried in a drying device at a temperature of 80-100℃ for 8 minutes to ensure that the ink is completely fixed and to prevent the glaze from turning white or cracking when the protective glaze is sprayed later.

[0067] Next, a water jet sprayer is used to apply the protective glaze slurry to the surface of the printed blank. The amount of glaze on the 400mm*600mm tray is 50g. After drying, a protective glaze layer is formed.

[0068] Finally, the body with the protective glaze layer is fired. The firing process includes a heating stage, a holding stage, and a cooling stage. In the heating stage, the temperature is increased to 1220-1250℃ at a heating rate of 5℃ / min. In the holding stage, the temperature is held at 1220-1250℃ for 10-20 minutes. In the cooling stage, the body is cooled to room temperature in the furnace to obtain dark skin glaze ceramic tiles.

[0069] Specifically, in this embodiment, during the heating stage, the temperature is increased to 1220-1250℃ at a rate of 5℃ / min to ensure uniform melting and interlayer bonding of the glaze layer. The thermal expansion coefficients of the three-layer glaze structure (surface glaze, skin glaze, and protective glaze) and the body are slightly different. If the temperature rises too quickly (e.g., exceeding 8℃ / min), instantaneous stress will occur between the body and the glaze layers due to the different rates of thermal expansion, potentially leading to glaze cracking or interlayer delamination. A low heating rate of 5℃ / min allows the temperature of each layer to rise synchronously, releasing stress slowly and ensuring tight interlayer bonding.

[0070] In this embodiment, during the heat preservation stage, the temperature is maintained at 1220-1250℃ for 10-20 minutes to achieve crystal phase stability, texture shaping, and color optimization. In the protective glaze layer, the apatite crystal phase (derived from bone ash) and the anorthite crystal phase (derived from calcite) continue to grow and disperse evenly during the heat preservation stage. The 10-20 minute heat preservation time ensures that the crystal phase particle size is controlled within 0.5-2μm; too small a particle size results in insufficient performance, while too large a particle size affects transparency, thus constructing a highly transparent reinforcing network. In the skin-like glaze layer, the heat preservation stage promotes the homogenization of the submicron liquid phase separation structure (barium-rich phase, silicon-rich phase), avoiding uneven gloss caused by insufficient local phase separation. Simultaneously, ZnO reacts fully with the ink pigment to form a stable coordination structure, enhancing color saturation. During the heat preservation process, micro-bubbles in the glaze layer (derived from raw material volatiles) can be slowly expelled, preventing residual bubbles after cooling. At the same time, the glaze maintains a certain fluidity, automatically repairing minor unevenness and ensuring a smooth glaze surface.

[0071] During the cooling stage, kiln-borne cooling refers to the natural cooling of the ceramic tiles within the kiln (cooling rate ≤ 5℃ / min), rather than forced air or water cooling. This process avoids: glaze cracking caused by thermal shock (if cooling is too rapid, the surface of the glaze layer may develop tensile stress due to rapid contraction, potentially leading to microcracks, especially due to the difference in thermal expansion between the crystalline and glassy phases in the protective glaze); destruction of the crystalline structure (the apatite crystalline phase in the protective glaze may develop defects due to lattice freezing during rapid cooling, reducing chemical stability); and color shift (ink pigments (such as iron black and cobalt blue) may become lighter in color due to non-equilibrium solidification during rapid cooling).

[0072] The present invention will be further explained and illustrated below through specific embodiments:

[0073] Example 1

[0074] A dark-colored skin-like glaze ceramic tile includes a base, a surface glaze layer, a skin-like glaze layer, an ink printing layer, and a protective glaze layer. The surface glaze layer, by mass percentage, comprises: 28.38% Al₂O₃, 56.90% SiO₂, 2.61% ZrO₂, 1.77% K₂O, 4.32% Na₂O, 2.31% CaO, 0.92% MgO, and 2.79% loss on ignition. The skin-like glaze layer, by mass percentage, comprises: 46.49% SiO₂, 15.64% Al₂O₃, 8.48% BaO, 3.98% ZnO, 5.44% CaO, and 5.31%... The protective glaze layer contains MgO, 4.03% K2O, 1.56% Na2O, and 9.07% loss on ignition; the raw materials of the protective glaze layer, by mass percentage, include: 40% potassium feldspar, 20% quartz, 15% calcite, 10% bone ash, 5% kaolin, and 10% zirconium silicate; the ink used in the ink printing layer, by mass percentage, includes: 35% pigment, 50% organic solvent, 5% dispersant, 8% humectant, and 2% pH adjuster, wherein the pigment is a mixture of iron black, cobalt blue, and lemon yellow pigments, the organic solvent is ethylene glycol, the humectant is glycerol, and the pH adjuster is ammonia. Its preparation method includes the following steps:

[0075] Preparation of the surface glaze slurry: The chemical composition of the surface glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.4, and ground until the residue passing through a 300-mesh sieve is less than or equal to 0.5%. The specific gravity of the surface glaze slurry is adjusted to 1.88 g / cm³. 3 spare;

[0076] Preparation of skin glaze: The chemical composition of the skin glaze layer and deionized water were added to a ball mill at a mass ratio of 1:0.35 and ground until the residue passing through a 200-mesh sieve was less than or equal to 0.8%. The specific gravity of the skin glaze was adjusted to 1.88 g / cm³. 3 spare;

[0077] Preparation of protective glaze slurry: The chemical composition of the protective glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.3, and ground until the residue passing through a 250-mesh sieve is less than or equal to 1%. The specific gravity of the protective glaze slurry is adjusted to 1.3 g / cm³. 3 spare;

[0078] Ink preparation: The chemical components of the ink are stirred and mixed evenly to obtain ink;

[0079] Preparation of the green body: Clay, quartz, and feldspar are used as raw materials for the green body. After crushing, they are mixed evenly, and the particle size distribution of the raw materials is controlled (D50 = 20-30μm) to ensure the plasticity of the green body. The mixed raw materials are put into a hydraulic molding machine, and 130MPa pressure is applied in a 600mm×1200mm mold to press into a dense green body. After molding, defects such as cracks and missing corners are removed. The molded green body is sent to a drying kiln and heated to 110℃ at a heating rate of 5℃ / min. It is dried for 50 minutes to reduce the moisture content of the green body to below 0.5%. During the drying process, the humidity in the kiln needs to be monitored to avoid brick shattering due to residual moisture during subsequent glazing. The dried green body is obtained.

[0080] Preparation of the surface glaze layer: The surface glaze slurry is applied to the surface of the dried body using a glazing process. For example, the amount of glaze applied is controlled to be 110g (corresponding to a 400mm×600mm tray) to ensure uniform coverage of the glaze layer with a thickness of about 0.3mm. The glaze layer is then dried at 180℃ for 15 minutes until the moisture content is ≤1% to form the surface glaze layer.

[0081] Preparation of skin glaze layer: Skin glaze slurry is applied to the surface of the glaze layer using a glazing process. Similarly, the amount of glaze applied is controlled to be 110g (corresponding to the amount of a 400mm×600mm tray). The glaze slurry forms a base layer with a submicron liquid phase separation structure through high temperature fluidity. After drying, the skin glaze layer is formed.

[0082] Preparation of the ink printing layer: A high-precision inkjet printer is used to print an ink pattern on the surface of the skin glaze. The printing parameters are set according to the ink characteristics, with the printhead temperature at 42℃ and the jet pressure at 0.4MPa. After inkjet printing, the ink is quickly dried by a drying device at a temperature of 90℃ for 8 minutes to ensure that the ink is completely fixed and to prevent the glaze from turning white or cracking when the protective glaze is sprayed later, thus forming the ink printing layer.

[0083] Preparation of protective glaze layer: The protective glaze slurry is sprayed onto the surface of the printed blank using a water jet device. The amount of glaze is 50g for a 400mm*600mm tray. After drying, a protective glaze layer is formed.

[0084] Finally, the body with the protective glaze layer is fired. The firing process includes a heating stage, a holding stage, and a cooling stage. In the heating stage, the temperature is increased to 1230℃ at a heating rate of 5℃ / min. In the holding stage, the temperature is held at 1230℃ for 15 minutes. In the cooling stage, the body is cooled to room temperature in the furnace to obtain dark skin glaze ceramic tiles.

[0085] The dark skin-colored glazed ceramic tile prepared in Example 1 is as follows: Figure 2 As shown, from Figure 2It can be seen that the ink has high color saturation, reaching the color level of traditional glossy glazes, with rich and pure colors, without any graying or whitening. Its gloss is controlled at 10-15°, achieving a soft satin finish, with a delicate and silky touch, retaining the characteristic texture of skin-like glazes. Its glaze surface has high flatness, meeting the standards for superior-grade porcelain tiles, with a smooth and flat surface. After testing, its acid resistance (1% HCl) and alkali resistance (1% NaOH) level reach AA grade, and its stain resistance passes the standard test, meaning the glaze surface is not easily corroded or contaminated by acids and alkalis. After 10 cycles of thermal shock at 150℃-20℃, there was no cracking, and the coefficient of thermal expansion matches the body well, with no cracking or other problems.

[0086] In this embodiment, the high-alumina and high-zirconium (28.38% Al2O3, 2.61% ZrO2) in the surface glaze layer forms a dense and chemically inert substrate, effectively preventing the upward migration of coloring impurities such as iron and titanium in the body, providing a pure and uniform canvas for inkjet printing and ensuring the pure color development of the ink; the combination of high-barium and high-zinc (8.48% BaO, 3.98% ZnO) and calcium and magnesium (5.44% CaO, 5.31% MgO) in the skin glaze layer forms a submicron-level liquid phase separation structure and a specific crystal phase structure, producing a soft, silky luster and a warm touch. At the same time, the introduction of ZnO stabilizes and enhances the color development of the ink; the introduction of bone ash in the protective glaze layer forms an apatite crystal phase, which works together with raw materials such as zirconium silicate and calcite to improve the chemical stability, thermal stability and hardness of the glaze surface, while ensuring the transparency of the glaze surface and not affecting the color development and texture of the underlying layer. The strictly controlled process parameters in this embodiment, such as firing temperature, firing cycle, glaze specific gravity and dosage, ensure good bonding and performance between the three glaze layers.

[0087] Example 2

[0088] A dark skin-colored glaze ceramic tile includes a base, a surface glaze layer, a skin-colored glaze layer, an ink printing layer, and a protective glaze layer. The formula differs from that of Example 1 in that the Al2O3 in the surface glaze layer is increased to 30%, while the remaining components are the same as those in Example 1, and the preparation method is also the same as that in Example 1.

[0089] The dark skin-colored glazed ceramic tile prepared in Example 2 is as follows: Figure 3 As shown, from Figure 3It can be seen that the ink color saturation has slightly improved, but the change is not particularly obvious; its gloss is still controlled at 8-12°, and the satin effect and touch are basically the same as in Example 1; its glaze surface has good smoothness, but is slightly uneven. After testing, its acid and alkali resistance level still reaches AA grade, and its anti-fouling performance is good; there is no cracking after thermal shock cycling. By comparing with Example 1, it can be found that the increase in Al2O3 content in the glaze layer further improves the glaze surface's refractoriness and chemical inertness, enhances the barrier effect on impurities in the body, and thus improves the ink color saturation to a certain extent; at the same time, due to the increase in Al2O3 content, the high-temperature viscosity of the glaze has increased, and the leveling property of the glaze surface is affected to some extent during firing, resulting in a slight decrease in smoothness, but still within an acceptable range.

[0090] Example 3

[0091] A dark skin-colored glaze ceramic tile includes a base, a surface glaze layer, a skin-colored glaze layer, an ink printing layer, and a protective glaze layer. The raw materials including the glaze layer, by weight percentage, include: 35% potassium feldspar, 20% quartz, 15% calcite, 10% bone ash, 5% kaolin, and 15% zirconium silicate. The remaining formulation is the same as in Example 1, and the preparation method is also the same as in Example 1.

[0092] The dark skin-colored glazed ceramic tile prepared in Example 3 is as follows: Figure 4 As shown, from Figure 4 It can be seen that the ink color saturation is comparable to that of Example 1, with pure color; its gloss is controlled at 8-12°, with a good satin finish and tactile feel; its glaze surface has high flatness, reaching the standard of superior grade. After testing, its acid and alkali resistance reaches AA level, with excellent anti-fouling properties; the corrosion resistance and stain resistance of the glaze surface are significantly improved compared to Example 1; no cracking occurred after thermal shock cycling; the glaze surface hardness is significantly improved, enhancing its resistance to scratches from everyday hard objects. Comparison with Example 1 reveals that the increased zirconium silicate content in the protective glaze layer significantly improves the hardness and scratch resistance of the glaze surface. Zirconium silicate has a Mohs hardness greater than 6, and as a hard phase, it is uniformly distributed in the glaze layer, enhancing the mechanical strength of the glaze surface; simultaneously, zirconium silicate also enhances the chemical stability of the glaze surface, improving its resistance to acid and alkali corrosion and staining; because the amount of zirconium silicate added is within a reasonable range, and other process parameters are properly controlled, it does not adversely affect the transparency and color of the glaze surface.

[0093] Comparative Example 1 (Traditional Single-Layer Glaze Structure)

[0094] A ceramic tile includes a base, a surface glaze, an ink printing layer, and a skin glaze layer, the formulations and preparation methods of which are the same as those in Example 1.

[0095] The ceramic tiles prepared in Comparative Example 1 are as follows Figure 5 As shown, from Figure 5 It can be seen that the ink has poor color development, with a pale and grayish color and low saturation, failing to reach the color development level of traditional glossy glazes. Its gloss is between 10-15°, and the satin effect and touch are similar to Example 1, but due to the color development problem, the overall texture is poor. The glaze surface smoothness is average, meeting the qualified product standard, but not as good as the superior product standard of Example 1. After testing, its acid and alkali resistance level is A, lower than the AA level of Example 1, and its stain resistance is also poor, with the glaze surface easily contaminated. A small amount of cracking occurred after thermal shock cycling. A comparison with Example 1 reveals that the traditional single-layer glaze structure cannot effectively prevent coloring impurities such as iron and titanium in the body from migrating upwards, causing these impurities to affect the color development of the ink and resulting in poor ink color. The formulation design of the single-layer glaze structure cannot provide a good color development environment for the ink pigments. At high temperatures, the pigment components are prone to volatilization, decomposition, or dissolution into the glass phase, leading to a lighter or grayer color. The physicochemical properties of the single-layer glaze structure are relatively poor, with lower chemical stability, thermal stability, and hardness compared to the three-layer glaze structure, thus affecting the overall performance of the ceramic tile.

[0096] Comparative Example 2 (Two-layer glaze structure)

[0097] A ceramic tile includes a base, a surface glaze layer, a skin glaze layer, and an ink printing layer, wherein the base, surface glaze layer, skin glaze layer, ink, and preparation method are the same as in Example 1.

[0098] The ceramic tiles prepared in Comparative Example 2 are as follows Figure 6 As shown, from Figure 6 It can be seen that the ink's color saturation is comparable to that of Example 1, with pure color; its gloss is controlled at 8-12°, with a good satin finish and tactile feel; its glaze surface has high smoothness, reaching the superior grade standard. After testing, its acid and alkali resistance is Grade A, but its stain resistance is poor, and the glaze surface is easily corroded and contaminated; it exhibits a certain degree of cracking after thermal shock cycling; its glaze surface has low hardness and is easily scratched. Comparison with Example 1 reveals that the surface glaze and satin glaze in the two-layer glaze structure provide a better color development environment and texture for the ink, but due to the lack of a protective glaze, the glaze surface has poor chemical stability, thermal stability, and hardness; lacking the crystalline reinforcement network of the protective glaze, the glaze surface has insufficient resistance to acid and alkali corrosion, thermal stress, and scratches, leading to problems during use.

[0099] Comparative Example 3 (Firing temperature decreased)

[0100] A ceramic tile includes a base, a surface glaze layer, a skin glaze layer, an ink printing layer, and a protective glaze layer. Its formula is the same as that of Example 1. The difference between the ceramic tile and Example 1 is that the temperature of the heat preservation stage is 1200℃, while the remaining steps are the same as those of Example 1.

[0101] The ceramic tiles prepared in Comparative Example 3 are as follows Figure 7 As shown, the ink's color saturation decreased, resulting in a lighter, grayish color, inferior to the color development effect of Example 1. Its gloss was slightly reduced, ranging from 8-12°, while the satin finish and tactile feel remained largely unchanged. The glaze surface had poor smoothness, exhibiting noticeable unevenness. Testing revealed that its acid and alkali resistance was Grade A, but its stain resistance decreased. Numerous cracks appeared after thermal shock cycling. The yield was low, approximately 70%. Comparison with Example 1 reveals that a firing temperature of 1200℃, below the optimal firing temperature of 1230℃, resulted in insufficient melting of the glaze, leading to decreased density and smoothness, and unevenness. Insufficient melting of the glaze resulted in weak bonding between the three glaze layers, affecting the physicochemical properties of the glaze, such as chemical stability, thermal stability, and hardness. Insufficient firing temperature also resulted in incomplete formation of crystalline phases in the glaze, particularly the apatite and anorthite phases in the protective glaze, leading to a decline in glaze performance and consequently affecting the ink's color development and the overall quality of the tile.

[0102] It is understood that those skilled in the art can make equivalent substitutions or modifications to the technical solution and inventive concept of the present invention, and all such substitutions or modifications should fall within the protection scope of the appended claims.

Claims

1. A dark skin-colored glazed ceramic tile, characterized in that, The product includes a base, a top glaze layer, a skin-like glaze layer, an ink printing layer, and a protective glaze layer. The chemical composition of the top glaze layer, by mass percentage, includes: 25-30% Al₂O₃, 50-60% SiO₂, 1-5% ZrO₂, 1-3% K₂O, 3-6% Na₂O, 1-3% CaO, 0.5-1% MgO, and 1-3% loss on ignition. The chemical composition of the skin-like glaze layer, by mass percentage, includes: 40-50% SiO₂...

2. 14-16% Al2O3, 6-10% BaO, 3-5% ZnO, 4-6% CaO, 4-6% MgO, 3-5% K2O, 1-3% Na2O, and 6-10% loss on ignition; the raw materials of the protective glaze layer, by mass percentage, include: 35-45% potassium feldspar, 15-25% quartz, 10-20% calcite, 5-15% bone ash, 3-8% kaolin, and 5-15% zirconium silicate.

2. The dark skin-colored glaze ceramic tile according to claim 1, characterized in that, The chemical composition of the surface glaze layer, by mass percentage, includes: 28.38% Al₂O₃, 56.90% SiO₂, 2.61% ZrO₂, 1.77% K₂O, 4.32% Na₂O, 2.31% CaO, 0.92% MgO, and 2.79% loss on ignition; the chemical composition of the skin glaze layer, by mass percentage, includes: 46.49% SiO₂, 15.64% K₂O, 4.32% Na₂O, 2.31% CaO, 0.92% MgO, and 2.79% loss on ignition. The protective glaze contains 8.48% Al2O3, 8.48% BaO, 3.98% ZnO, 5.44% CaO, 5.31% MgO, 4.03% K2O, 1.56% Na2O, and 9.07% loss on ignition; the raw materials of the protective glaze, by mass percentage, include: 40% potassium feldspar, 20% quartz, 15% calcite, 10% bone ash, 5% kaolin, and 10% zirconium silicate.

3. A method for preparing a dark skin-colored glazed ceramic tile as described in any one of claims 1-2, characterized in that, Including the following steps: The chemical composition of the glaze layer is fed into a ball mill according to the formula ratio, and deionized water is added for ball milling to obtain the glaze slurry. The chemical composition of the skin glaze is put into a ball mill according to the formula ratio, and deionized water is added for ball milling to obtain skin glaze slurry. The raw materials for the protective glaze are put into a ball mill according to the formula ratio, and deionized water is added for ball milling to obtain the protective glaze slurry. A glaze slurry is applied to the surface of the body using a glazing process, and a glaze layer is formed after drying. A skin-like glaze is applied to the surface of the glaze layer using a glazing process, and after drying, a skin-like glaze layer is formed. Ink is printed onto the surface of the skin's enamel layer using inkjet printing to form an ink-printed layer. A water jet sprayer is used to apply the protective glaze slurry to the surface of the printed blank, which then dries to form a protective glaze layer. The body with the protective glaze layer is fired to obtain the dark skin glaze ceramic tile.

4. The method for preparing dark skin-colored glazed ceramic tiles according to claim 3, characterized in that, In the preparation of the surface glaze slurry, the chemical composition of the surface glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.4, and ground until the residue passing through a 300-mesh sieve is less than or equal to 0.5%. The specific gravity of the surface glaze slurry is adjusted to 1.85-1.9 g / cm³. 3 spare.

5. The method for preparing dark skin-colored glazed ceramic tiles according to claim 3, characterized in that, In the preparation of the skin enamel slurry, the chemical composition of the skin enamel layer and deionized water are added to a ball mill at a mass ratio of 1:0.35, and ground until the residue passing through a 200-mesh sieve is less than or equal to 0.8%. The specific gravity of the skin enamel slurry is adjusted to 1.85-1.9 g / cm³. 3 spare.

6. The method for preparing dark skin-colored glazed ceramic tiles according to claim 3, characterized in that, In the step of printing ink onto the skin's enamel surface using inkjet printing to form an ink-printed layer, printing parameters are set according to the ink characteristics, with the printhead temperature at 40-45℃ and the jet pressure at 0.3-0.5MPa.

7. The method for preparing dark skin-colored glazed ceramic tiles according to claim 3, characterized in that, In the step of preparing the protective glaze slurry, the chemical composition of the protective glaze layer and deionized water are added to a ball mill at a mass ratio of 1:0.3, and ground until the residue passing through a 250-mesh sieve is less than or equal to 1%. The specific gravity of the protective glaze slurry is adjusted to 1.2-1.4 g / cm³. 3 spare.

8. The method for preparing dark skin-colored glazed ceramic tiles according to claim 3, characterized in that, The firing process for the green body to form the protective glaze layer includes a heating stage, a holding stage, and a cooling stage. In the heating stage, the temperature is increased to 1220-1250℃ at a heating rate of 5℃ / min. In the holding stage, the temperature is held at 1220-1250℃ for 10-20 minutes. In the cooling stage, the green body is cooled to room temperature in the furnace.